Designing the operation monitor of battery of the generator in the base transceiver station - Nguyen Thị Xoan; Tran Văn Bình; Hà Ngọc Thuan; Bạch Văn Nam (Computer Science and Information Technologies, 2022)
The base transceiver station (BTS)'s continuous power supply has been the subject of a lot of research. The majority of research focuses on increasing power usage effectiveness or adding solar battery systems for BTS stations. Due to the geographical conditions in the North of Vietnam, solar cell efficiency is rather poor and the investment cost is quite high, therefore BTS stations are still relying mostly on battery and generator backup systems. This article presents a design solution to designing the operation monitor of battery of the generator in the base transceiver station. From solution design, the authors designed the hardware and software. The device allows communication and sends alarms to the base transceiver station (BTS) manager. Through the testing process, the system has met the requirements of the problem and is easily integrated into the BTS.